Innovative Bamboo Bowling Game to Improve Motor Skills in Early Childhood - Anak Agung Ayu Mega Laksmi Febriantari; Anadhi, I Made Gede; Sindu Putra, Ida Bagus Komang (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The need for educational game tools to stimulate children's gross motor skills is one of the limitations of teachers. This research aims to create an innovative bamboo bowling game to improve children's gross motor skills. The research method uses the ADDIE approach development method. Observation, interviews, and literature collected data. The research subjects consisted of 3 experts in relevant fields. The tool used to analyze research results is a questionnaire. This research was analyzed descriptively and quantitatively using Lawshe's content validation formula, the Content Validity Ratio (CVR). From the results of the expert assessment, the CVR value obtained was 0.99, and the CVI value was 0.99. All media experts gave a CVR value of 0.99. Therefore, Innovative Bamboo Bowling is considered valid. Based on these findings, Innovative Bamboo Bowling is suitable for early childhood learning activities in developing gross motor skills and can have goals that focus on improving children's physical and cognitive skills in a fun and beneficial environment. The implications of this research can be the basis for developing intervention programs or gross motor stimulation activities that are more effective and targeted.